Chain for Strengthening Work Readiness - Fataron, Zuhdan Ady; Sijabat, Rauly (Dinamika Pendidikan, 2019)
This study aimed to empirically examine the work readiness model developed in this study by using a variable approach to training, apprenticeship, self efficacy and locus of control. Data on training variables, apprenticeship, self efficacy, locus of control, and work readiness were obtained through interviews using a questionnaire conducted to the final semester students of the Faculty of Islamic Economics and Business of Walisongo State Islamic University (UIN Walisongo Semarang). The sample selection was conducted using a purposive random sampling approach in order to obtain a total of 112 respondents. Testing the research model was done by using SEM as an approach to the analysis technique. The test results showed that training and apprenticeship were proven to be able to explain self-efficacy and locus of control. The results of this study also showed that training, apprenticeship, self efficacy and locus of control were appropriate variables to explain variations in work readiness. Square Multiple Correlation value on work readiness variable was 33.5%. Based on the findings of this study, the suggestion for future research is to develop a research model by testing the self-concept variables and fear of failure to work readiness.